Ergonomic Risk Evaluation to Minimize Musculoskeletal Disorders in SMEs Leather Shoes at Indonesia - Indah Pratiwi; Tiara Adhitama (Jurnal Ilmiah Teknik Industri, 2022)
This study was carried out at SME for the purpose of making leather shoes in the manufacturing process. Pattern, upper printing, finishing, and 16 other workstations are among the three workstations. Production operations are performed manually in a seated position that includes squatting, bending, or standing position that is repeated, and workers operate at average to rapid speeds for 7 hours each day. This signifies that the action is hazardous and may result in Musculoskeletal Disorders (MSDs). The Job Strain Index (JSI) and Muscle Fatigue Assessment (MFA) methodologies will be used in this study to identify working posture conditions. The MFA method is used to analyze the level of effort, duration of labor, and frequency of work motions in order to determine muscle tiredness in each section of the worker's body. The 14 activities were subjected to the JSI method investigation, and the high risk was achieved by printing the top right hand SI 20.25 and installing the right-hand sole 13.5. The MFA approach was used to accept high to extremely high-risk body parts, such as the back, neck, and right hand, and make recommendations for how to reduce muscle fatigue in each body part. The findings of this study can be used to improve the upper printing station's design, as well as the table design for designing and drawing patterns and the chair design for sewing activities.